Epidemiological Features and Clinical Repercussions of Supernumerary Teeth in a Multicenter Study: A Review of 518 Patients with Hyperdontia in Spanish Population - Brinkmann, Jorge Cortés-Bretón; Martínez-Rodríguez, Natalia; Martín-Ares, María; Sanz-Alonso, Javier; Marino, Juan Santos; Suárez García, Maria Jesús; Dorado, Cristina Barona; Martínez-González, Jose María (European Journal of Dentistry, 2020)
Objectives The aim of this study was to establish the prevalence of supernumerary teeth (ST) in a sector of the population of Madrid, as well as possible complications associated with the presence of these teeth.Materials and Methods The study investigated patients (n = 28,114) who sought dental care at the Oral Surgery Service of three different centers between May 2005 and April 2018. Cases that did not present this numeric dental developmental variation were discarded, registering only those presenting ST.Statistical Analysis Statistical analysis consisted of univariate analysis (mean, standard deviation, median, etc.), bivariate analysis applying the chi-squared test, whereby statistical significance was established with a confidence interval (CI) of 95% (p < 0.05), and multivariate analysis by means of classification and decision trees.Results The study found ST in 518 patients, representing a prevalence of 1.84%. The 518 patients presented a total of 726 ST. Distomolars were the most common, representing 37.7% of the sample, followed by premolars (20.1%). About 70.5% of the sample were located in the maxilla and 78% of ST were impacted. Radiographs revealed that 39.7% of STs were associated with disorders. Supplementary morphology appeared in 52.1% of the sample.Conclusions Although mesiodens is considered the most common ST, the present study found distomolars and supernumerary premolars to be the most frequently occurring. Pathology was associated with 39.7% of the ST sample. Early diagnosis allows optimal patient management and treatment planning, with intervention at an appropriate time to prevent complications in development and so reduce later treatment need.
Keywords: clinical repercussions; epidemiological features; multicenter study; Spanish population; pathology; supernumerary teeth